An accumulative model for the comparative life cycle assessment case study iron and steel process. - Li, Guiqi
Life cycle assessment is a powerful tool in the evaluation of the environmental performance. However, there is no generally accepted methodology. To develop a practical method, an accumulative model for the comparative life cycle assessment is established and applied in the two typical iron and steel processes, the DRI/EF process and the BF/BOF process. The results indicate that the method could quantitatively compare the alternatives. When the DRI/EF process is compared with the BF/BOF process, it is shown that the IREI (integrated relative environmental index) is 60.22 percent for the production of iron and 52.4 percent for the production of steel, respectively. The environmental performance of the DRI/EF process is superior to that of the BF/BOF process.
Keywords: Accumulative model; BF/BOF process; DRI/EF process; Environmental equivalent coefficient (EEC).; Environmental factor; Integrated relative environmental index (IREI).; Life cycle assessment (LCA).; Weighting factor